1996
DOI: 10.2527/1996.742310x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of flake density on the feeding value of steam-processed corn in diets for lactating cows.

Abstract: Four primiparous Holstein cows (112 d in lactation) with cannulas in the rumen and proximal duodenum were used in a 4 x 4 Latin square design. Dry-rolled (DR) corn (density .52 kg/L) was compared with stream-flaked (SF) corn processed to three flake densities: .39, .32, and .26 kg/L. The basal diet contained (DM basis) 43.4% alfalfa hay, 39.5% corn (DR or SF), 2.2% yellow grease, 9.6% cane molasses, .7% sodium bicarbonate, and 4.6% protein-mineral supplement. Steam flaking increased DM intake (P < .01). There … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
1
25

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(73 citation statements)
references
References 21 publications
4
43
1
25
Order By: Relevance
“…Maiores taxas de hidrólise in vitro do amido processado por floculação, em comparação ao amido do grão moído ou laminado, têm sido reportadas na literatura (Chen et al, 1995;Plascencia & Zinn, 1996;Joy et al, 1997;Yu et al,1998).…”
Section: Resultsunclassified
“…Maiores taxas de hidrólise in vitro do amido processado por floculação, em comparação ao amido do grão moído ou laminado, têm sido reportadas na literatura (Chen et al, 1995;Plascencia & Zinn, 1996;Joy et al, 1997;Yu et al,1998).…”
Section: Resultsunclassified
“…On the other hand, some studies (Harvantine et al, 2002) observed a decrease in DMI when SFC corn replaced DR corn in diet. Others, observed an increase in DMI when SF corn was compared to finely ground (Yu et al, 1998) or DR corn (Plascencia and Zinn, 1996), however, most researchers reported no difference in DMI among cows fed DR or SF corn (Theurer et al, 1999). Similar to the results obtained in previous digestion trials (Joy et al, 1997), milk yield was not affected by method or degree of corn processing.…”
Section: Dr-mg and Dr-cg)mentioning
confidence: 99%
“…Increasing the intensity of processing, decreased the density of grain and increased the extent of total tract digestion of starch (Plascencia and Starch is a primary Source Of energy in ruminant diets and represents 70 to 80% of most grains that are fed to high producing dairy cows' The for Zinn, 1996; J o y e t al., 1997). However, et al., 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Esse fato está de acordo com a ausência de efeito do processamento na digestão de CNF e no teor de NDT das dietas. Aumento na produção de propionato, redução na concentração de N-NH3 e no pH ruminal são respostas típicas em vacas alimentadas com dietas com maior concentração de carboidratos fermentáveis (PLASCENCIA; ZINN, 1996;JOY et al, 1997;KNOWLTON et al 1998;FIRKINS et al, 2001) o que não ocorreu no presente estudo. Plascencia e Zinn (1996) avaliando milho floculado e milho laminado não relataram diferença no PH ruminal, resultado semelhante foi descrito por Oliveira et.…”
Section: Resultsunclassified